Promoting Environmental Stewardship and Public Health: A Comprehensive Community Service Initiative - Ester Julinda Simarmata; Rosdiana Samosir; Fitri Almy Tujza; Syahriatul Lisma; Rosdiana; Synta Rinjani Sirait; Supriati; Suzanna Indra; Sulastri Pasaribu; Sulastri (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The socialization sessions, characterized by a structured mix of material presentations (30%) and interactive discussions (70%), served as an educational platform for primary school students to understand the importance of maintaining a clean and health-conscious lifestyle. Subsequent field activities engaged participants in collaborative problem-solving efforts, primarily realized through synchronized cleaning initiatives in the school environment and the introduction of technologically advanced automated trash cans. In addition, the project incorporated technological innovation by introducing automated trash cans, which were strategically designed to capture the interest of the students and provide essential knowledge on proper waste disposal practices. The findings underscore the efficacy of a nuanced approach that combines educational efforts, practical efforts, and technological interventions in shaping sustainable behavior among the younger generation, thereby positively impacting the broader community environment.